Van Gogh's Painting and an Incestuous Universe: why Wahlberg's Critique is Insufficient - Søvik, Atle Ottesen (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2023)
This article continues a discussion the authors have had with Mats Wahlberg on evolutionary theodicies. We have previously suggested a theodicy where there are token unique goods that could only have been actualized through indeterministic evolution. Wahlberg objects that we cannot appeal to such goods, since given indeterminism, God cannot know that such goods will appear. In this article we respond by arguing that God can know well enough that certain kinds of token goods will appear, without knowing in detail their specific character, or when they will happen.